Grammatical and stylistic particularities in Livy’s work - Ana-Maria POPESCU POPA (Diversitate si Identitate Culturala in Europa)
In this article we have conducted a number of grammatical and stylistic analyses on representative fragments from the monumental work of Livy. This analysis aims at discovering the particularities of construction in different types of texts, such as: Praefatio –the appeal to method, individual and collective portraits, discourses and battle scenes.